Identification of a novel BCL2‐specific inhibitor that binds predominantly to the BH1 domain. (17th August 2016) - Iyer, Divyaanka; Vartak, Supriya V.; Mishra, Archita; Goldsmith, Gunaseelan; Kumar, Sujeet; Srivastava, Mrinal; Hegde, Mahesh; Gopalakrishnan, Vidya; Glenn, Mark; Velusamy, Mahesh; Choudhary, Bibha; Kalakonda, Nagesh; et al.
Abstract : The antiapoptotic protein BCL2 is overexpressed in several cancers and contributes to prolonged cell survival and chemoresistance, lending itself as an excellent target for cancer therapy. Here, we report the design, synthesis, and characterization of Disarib, a novel BCL2 inhibitor. Disarib showed selective cytotoxicity in BCL2 high cancer cell lines, and CLL patient primary cells, as compared to BCL2 low cell lines. BCL2 knockdown in cells rendered remarkable resistance to Disarib, while sensitivity was regained upon its ectopic expression, establishing target specificity. In silico, biochemical and biophysical studies demonstrated strong affinity of Disarib to BCL2, but not to other antiapoptotic BCL2 family members viz., BCL‐xL, BCL2A1 etc. Interestingly, biophysical studies showed that BH1 domain deletion mutant demonstrated ~ 67‐fold reduction in BCL2‐Disarib interaction, while it was only ~ 20‐fold in the case of BH3 deletion mutant, suggesting predominant involvement of the BH1 domain for Disarib binding. Thus, we report identification of a novel BCL2 inhibitor with a unique mechanism of BCL2 inhibition, as opposed to the well‐studied BH3 domain targeting. Abstract : We describe design, synthesis, and characterization of a novel BCL2 inhibitor, Disarib, which inhibits cancer cell proliferation in a BCL2‐dependent manner. Disarib predominantly targets the BH1 domain, unlike other BCL2 inhibitors reported so far. Importantly, it specifically binds to the target, sparing other members of BCL2 family.